If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4n-(3n+6)=-1
We simplify the equation to the form, which is simple to understand
4n-(3n+6)=-1
Remove unnecessary parentheses
4n-3n-6=-1
We move all terms containing n to the left and all other terms to the right.
+4n-3n=-1+6
We simplify left and right side of the equation.
+1n=+5
We divide both sides of the equation by 1 to get n.
n=5
| 16-a=-4(6a+1)+3a | | 21x-2=18x+30 | | -7(7+5b)=23+b | | 12n=12 | | 3g^2(4g-7)= | | a/8-1=a/3-7/12 | | r+4.2=8.3 | | 4y^3+5y^2-6y^3-7y+19y^3= | | 19+7x=7+6(7x+2) | | 3x+15=123 | | 5x-11y=3 | | 4(d-2)=2(d+2) | | 9+7x=7x+6 | | 0.4n+2.7=5.1 | | -7n-26=-3(7+4n) | | 4(d-2)=(d+2) | | 2(4x+x)=15x-10 | | d+4=2+3d-.5 | | 3x-2+18x=18x+12+1 | | (4x-10)+(2x+20)=180 | | (3-11y)-(17+12y)= | | 2(4x+4)=15x-10 | | 31-7p=3(p+7) | | 5y(y^2-7y^3)= | | 3=-2-5k | | 1+7(3p+4)=15+7p | | 5-3z-18=z-1+8x | | 6(3x-5)-2(-6x+4)= | | -(-2x-8y-3)= | | 4x+9=x+4+8x | | 2x-3x=12 | | 2(9y-10)=40 |